(untitled) (Lundiana: International Journal of Biodiversity, 2008)
The butterfly fauna of a small forest fragment in the campus of the Pontifícia Universidade Católica de Minas Gerais was surveyed between March and November 2001. The adult butterflies were captured using hand nets and frugivorous traps. In addition, caterpillars were raised in the laboratory for identification after emergence. Ninety-one species of six families were recorded. Among them, 46.1% belonged in Nymphalidae; 28.5% in Hesperiidae; 15.4% in Pieridae; 4.4% in Riodinidae; 4.4% in Papilionidae; and 1.1% in Lycaenidae. At least 28.6% of the species are common in urban and other disturbed environments in Brazil and no rare or endangered species was recorded. On the other hand, the species in this fragment represent 18.7% of the species known to occur in the vicinities of the city of Belo Horizonte. Moreover, species of taxa considered as indicators of preserved environments, although in small absolute numbers, occurred in proportions similar to those found in large forest remnants across Brazil. It is concluded that the studied fragment, as well as other small urban fragments, are important refuges for conservation of butterflies within cities.